2004
DOI: 10.2209/tdcpublication.45.99
|View full text |Cite
|
Sign up to set email alerts
|

Application of "Prescale" as an Aid to Clinical Diagnosis in Orthodontics

Abstract: We examined the feasibility of applying the Dental Prescale Occluzer System ™ to the evaluation of occlusion in orthodontic patients. The patients were classified according to the type of malocclusion or facial pattern. The values of occlusal contact area and occlusal force obtained from these individuals differed depending on the type of occlusion or facial pattern. These values were higher in individuals with normal occlusion than in patients with malocclusion and higher in patients with the Brachyo facial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Males have thicker masseter muscle and stronger occlusal force than females [34, 35], and subjects with strong occlusal force presented with a brachyfacial pattern [36, 37], as observed in our male subjects. Therefore, differences in the tested measurements between sexes observed in this study may be caused by the discrepancy in occlusal force generated by the masseter muscle.…”
Section: Discussionmentioning
confidence: 55%
“…Males have thicker masseter muscle and stronger occlusal force than females [34, 35], and subjects with strong occlusal force presented with a brachyfacial pattern [36, 37], as observed in our male subjects. Therefore, differences in the tested measurements between sexes observed in this study may be caused by the discrepancy in occlusal force generated by the masseter muscle.…”
Section: Discussionmentioning
confidence: 55%
“…12 In a previous study, occlusal contact area and force were reported to be greater in male patients than in female patients. Further, the occlusal contact area was reported to be larger in patients aged 40 years, while there was no statistically significant difference in the occlusal contact area among the three age groups (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and 31-40 years).…”
Section: Discussionmentioning
confidence: 91%
“…In addition, taking into account studies suggesting a correlation between vertical skeletal pattern, occlusal force, and occlusal contact area, the mandibular plane and gonial angles were incorporated into the linear mixed model as covariates. 17,18 Patients with a temporomandibular joint disorder often have poor masticatory function. 20 Therefore, patients diagnosed with temporomandibular joint disorders based on the questionnaires administered at the first visit or clinical and radiographic examination were excluded from the study.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kitafusa 9) , occlusal force, occlusal contact area, and average occlusal pressure are greatest in cases of mandibular prognathism, crowding, maxillary prognathism, cross bite, and open bite, in that order. Among the present 14 patients undergoing further occlusal force evaluation after 1 year or more of retention, 2 showed large occlusal forces of ≥900 N at pre-treatment, and both were cases of mandibular prognathism.…”
Section: Dental Prescale Measurement Resultsmentioning
confidence: 99%